An introduction to optoelectronic sensors - Righini, Giancarlo C.; Tajani, Antonella; Cutolo, Antonello (Series in optics and photonics ;, 2009)
This invaluable book offers a comprehensive overview of the technologies and applications of optoelectronic sensors. Based on the R & D experience of more than 70 engineers and scientists, highly representative of the Italian academic and industrial community in this area, this book provides a broad and accurate description of the state-of-the-art optoelectronic technologies for sensing. The most innovative approaches, such as the use of photonic crystals, squeezed states of light and microresonators for sensing, are considered. Application areas range from environment to medicine and healthcare.